Thirty-year retrospective on language, gender and sexuality research. (23rd December 2021) - Hall, Kira; Borba, Rodrigo; Hiramoto, Mie
Abstract : This thirty-year retrospective on language, gender and sexuality research, launched in anticipation of the thirtieth anniversary of the 1992 Berkeley Women and Language Conference, showcases essays by luminaries who presented papers at the conference as well as allied scholars who have taken the field in new directions. Revitalising a tradition set out by the First Berkeley Women and Language Conference in 1985, the four biennial Berkeley conferences held in the 1990s led to the establishment of the International Gender and Language Association and subsequently of the journal Gender and Language, contributing to the field's institutionalisation and its current panglobal character. Retrospective essays addressing the themes of Politics, Practice, Intersectionality and Place will be published across four issues of the journal in 2021. The final issue of our thirty-year retrospective shows how studies of language, gender and sexuality may be enlivened by seriously engaging with the notion of place – understood as one's geographical location, locus of enunciation and/or position within the field. Bonnie S. McElhinny and María Amelia Viteri scrutinise lingering effects of colonialism and advocate for hope as a central affective dimension of decolonial practice. Drawing upon Black feminisms, Busi Makoni discusses the embodiment of refusal to racialised forms of patriarchy and Sonja L. Lanehart underlines the importance of bringing African American Women's Language more centrally into the field's remit. The next three essays move their foci to specific regions: Pia Pichler reflects on the entanglement of place, race and intersectionality in the UK; Janet S. Shibamoto-Smith warns against the dangers of reifying essentialised categories in Japanese language and gender research; Fatima Sadiqi criticises the underrepresentation of North Africa in the field by reviewing the emergence and resilience of feminist linguistics in the region. The two final essays highlight the importance of sociolinguistic activism and the urgent need of moving beyond the field's Global North emphasis. Amiena Peck discusses the power of digital activism and the way it has reignited her passion for engaged scholarship. Ana Cristina Ostermann advocates for micro-interactional analysis as a method for illuminating Southern epistemologies of gender and sexuality. The theme series also pays tribute to significant scholars present at the 1992 Berkeley conference who are no longer with us; in this issue, Rusty Barrett and Robin Queen offer a lively account of the life and work of linguist and novelist Anna Livia.